Study On The Use Of Oral Drills And Role-Play Method In Improving Students’ Interactive Speaking Achievement - Sinambela, Kelvri L.; Simanjuntak, Debora Chaterin (LPPM Universitas Advent Indonesia, 2017)
This study examines whether the use of Oral Drills and Role-Play method could improve students’ interactive speaking achievement. This study used quantitative research using pre-experimental method with one group pre and posttest design. The study was conducted in SMP Advent II, Setia Budi, Bandung. The participants of this study were 30 students from the first year students at SMP Advent II Setia budi, Bandung as the sample and they were grade VII at SMP Advent II Setia Budi, Bandung. This study used one experimental group as the sample. A pre-test and post-test were done. The experimental group was given treatment (Oral Drill and Role-Play Method). The data gathered was then statistically calculated and analysed. According to the interpretation, if p Value (Sig.) - (0.05) then HA is accepted and H0 is rejected and If p Value (Sig.) - (0.05) then H0 is accepted and HA is rejected. After calculating the data it was known that the p-value = 0.000 lesser than alpha 0.05. Result of the study showed that there is a significant difference in improving students’ interactive speaking achievement after using oral drills and role-play method.Keywords: Interactive Speaking, Oral Drills, Role-Play Method